CD10 expression in gastric carcinoma is correlated with tumor grade and survival - Jafarian, Amir Hosein; Kooshki Forooshani, Melika; Takallou, Leila; Mohamadian Roshan, Nema (Faculty of Medicine, Trisakti University, 2019)
BackgroundGastric carcinoma (GC) is the most common non-skin malignancy in Iranian men and the second leading cause of cancer-related mortality. Invasion and metastasis are considered as the major causes of cancer-related morbidity and mortality. Proteinases such as matrix metalloproteinases play an important role in tumor progression and mediating extracellular matrix remodeling. CD10 is a 90-110kd cell surface zinc-dependent metalloproteinase and there is evidence that this membrane protein may facilitate invasion and/or metastasis of tumoral cells. The objective of this study was to determine the frequency of CD10 expression in the stromal cells of GC and determine its relationship with survival and clinicopathological factors. MethodsA cross-sectional study was performed involving 50 patients with histopathologic diagnosis of GC. CD10 expression was determined by immunohistochemistry (IHC). Survival of the patients as well as the grade and stage of the tumors and demographic variables were documented. The Kaplan-Meier test was used for data analysis.ResultsStromal CD10 was detected in 46% of the GC stromal cells. No immunoreactivity was identified in the stromal cells of normal adjacent tissue. Stromal CD10 expression in gastric carcinoma did not correlate with the age and gender of the cases as well as the size and location of the tumor, and lymph node involvement but correlated with tumor stage (p=0.01), tumor grade(p=0.01) and patients’ survival (p=0.02). ConclusionStromal CD10 expression is correlated with tumor differentiation, clinical stage and survival in GC. CD10 expression could be considered as a negative prognostic factor for gastric carcinoma.